Advances in the improvement of thermal-conductivity of phase change material-based lithium-ion battery thermal management systems: An updated review. (September 2022) - Mitra, Abhijeet; Kumar, Rajan; Singh, Dwesh Kumar; Said, Zafar
Abstract: A battery thermal management system (BTMS) that relies on phase change materials (PCMs) seems to be a prominent system of cooling for assuring the safety, reliability, durability, and functionality of lithium-ion batteries (LIBs). However, PCM-based BTMSs cannot keep battery temperatures within safe limits at higher charging or discharging rates due to the low thermal conductivity ( k ) of these materials. The present study explores the effect of various k enhancers for the PCM-based BTMSs to improve the cooling performance of these systems. The study includes a comprehensive review of the use of metal and carbon-based enhancers in PCM-based BTMSs. PCM-based BTMSs include pure PCM, composite phase change material (CPCM), and hybrid PCM-based BTMS. Maximum increased temperature, temperature difference, and percentage reduction in maximum battery temperature rise are the key metrics used to evaluate the performance of the BTMS. Furthermore, the effects of several parameters, including discharge rate, coolant inlet velocity, mass, and thickness of PCM, as well as different concentrations and types of k enhancers on the thermal management of LIBs, are thoroughly investigated. Different carbon and metal-based enhancer are discussed, among which carbon nanofibre (CNF) shows best results, whereas, in metals, Ag nanoparticles seems to be best, excluding its economics. This review paper also discusses future research directions and challenges in this trending topic. The paper provides a better understanding of the fundamentals and perceptions of different types and shapes of k enhancers for PCM-based BTMS of LIBs in terms of improved thermal performance (TP). Graphical abstract: Unlabelled Image Highlights: Different BTMSs are discussed in brief. The comprehensive review of carbon-based thermal conductivity enhancers of PCM-based BTMS is carried out. The comprehensive review of metal-based thermal conductivity enhancers of PCM-based BTMS is carried out. This review paper also discusses future research directions and challenges in this trending topic.